2011
DOI: 10.3758/s13414-011-0189-4
|View full text |Cite
|
Sign up to set email alerts
|

Memory for sound, with an ear toward hearing in complex auditory scenes

Abstract: An area of research that has experienced recent growth is the study of memory during perception of simple and complex auditory scenes. These studies have provided important information about how well auditory objects are encoded in memory and how well listeners can notice changes in auditory scenes. These are significant developments because they present an opportunity to better understand how we hear in realistic situations, how higher-level aspects of hearing such as semantics and prior exposure affect perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 38 publications
(30 citation statements)
references
References 129 publications
(169 reference statements)
3
27
0
Order By: Relevance
“…Although performance on this task declines when there is a larger time interval between the to-be-discriminated tones and when there is a larger number of masking tones, these two factors do not interact in such a way that memory for the first tone declines precipitously for more complex sounds (Demany Semal, Cazalets, & Pressnitzer, 2010a;Demany, Trost, Serman, & Semal, 2008), as is the case with vision (Phillips, 1974). An important limitation to these studies, however, is that the memory system recruited for detection of frequency shifts might be different from the memory system(s) involved in implicit or explicit comparisons between complex auditory scenes (including ABA-patterns) (Demany, Semal et al, 2010b; for further discussion, see Snyder & Gregg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although performance on this task declines when there is a larger time interval between the to-be-discriminated tones and when there is a larger number of masking tones, these two factors do not interact in such a way that memory for the first tone declines precipitously for more complex sounds (Demany Semal, Cazalets, & Pressnitzer, 2010a;Demany, Trost, Serman, & Semal, 2008), as is the case with vision (Phillips, 1974). An important limitation to these studies, however, is that the memory system recruited for detection of frequency shifts might be different from the memory system(s) involved in implicit or explicit comparisons between complex auditory scenes (including ABA-patterns) (Demany, Semal et al, 2010b; for further discussion, see Snyder & Gregg, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Because the noises are unlikely to be perceived as auditory objects prior to the first time they are successfully segregated, this result suggests that short-term memory traces are able to automatically facilitate segregation. Finally, studies of streaming context effects have shown that both prior stimuli and prior perception of those stimuli can have large effects on a subsequent perceptual decision, an example of implicit memories influencing perception (Snyder et al, 2008, 2009a,b; Snyder and Weintraub, 2011; for similar findings in continuity perception, see Riecke et al, 2009, 2011; for related research in speech perception, see McClelland et al, 2006). In particular, a prior ABA- pattern with a large Δ f biases following patterns to be heard as one stream, a contrastive or suppressive effect; in contrast, prior perception of two streams biases subsequent patterns to be heard with the same percept, a facilitative effect.…”
Section: Auditory Scene Analysis As a Framework To Study Awarenessmentioning
confidence: 99%
“…While a large body of psychological and neurophysiological research has demonstrated how we segregate and group relatively simple acoustic patterns into auditory object representations (Bregman, 1990;Snyder and Alain, 2007), much less is known about how much of the information we can process and remember. Recent research has shown that the substantial amount of information to process within a typical acoustic scene gives rise to change deafness, the inability to detect rather large changes to objects in auditory scenes (e.g., object deletions or replacements; for a review see Snyder and Gregg, 2011;Snyder et al, 2012). Empirical investigations of change deafness have shown that listeners fail to hear changes in speech (Vitevitch, 2003), music (Agres and Krumhansl, 2008), and environmental sounds (e.g., Eramudugolla et al, 2005;Gregg and Samuel, 2008).…”
Section: Introductionmentioning
confidence: 97%